Evaluation of Mutual Fund Performance and Advisory Fees in China - Sun, Lu (2007)
When people invest in mutual funds, they invest in talents of portfolio management. They obtain return from mutual funds active strategies and pay for the service of their investment advisor at the same time. This paper aims to evaluate the mutual fund performance and advisory fees in China to shed light on the answer to the question of whether it is rational to invest in mutual funds in China.